MULTICULTURAL EDUCATION: Effort in Overcoming Problems of Cultural Conflict in Indonesia - Muhammad Rasyid Ridho; Tumin Tumin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The purpose of the study was to determine the concept of multicultural education, multicultural education for conflict resolution, the implementation of multicultural education in educational units, and the decision of the curriculum of multicultural education. This study uses a qualitative description method with the nature of research literature research. As a result of this study, people respect each other more because the concept of multicultural education aims to provide solutions and minimize conflicts caused by multidimensional and heterogeneous social situations. Can understand that respect unity and justice diversity context. Multicultural education basically exists to deal with conflict phenomena in multicultural societies. Multicultural education should be applied as soon as possible and also focus on the values that exist in society, rather than focusing solely on the knowledge aspect. The multicultural education curriculum needs to actually present important content that explains the perspectives of many people, based on the assumption that there is no unified interpretation of historical truth, emphasizing different cultural perspectives. Advocates the principles of unity and unity and provides an understanding of cultural differences.